Silica analysis in bamboo black liquor by ICP-AES with the assistance of microwave digestion. (25th July 2017) - Zhang, Weipeng; Xu, Yongjian; Duan, Chao; Zhang, Dingjun
Abstract : Combination of ICP-AES with a HNO3 /H2 O2 /HF digestion technique is a new approach for the determination of silica content in bamboo black liquor. Abstract : Herein, a facile and reliable approach for the determination of silica content in bamboo lignocellulosic waste liquid (black liquor) by inductively coupled plasma atomic emission spectrometry (ICP-AES) in combination with microwave digestion was demonstrated. The results showed that black liquor samples pretreated in a microwave-assisted digestion system with the digestion solution contaning HNO3, H2 O2, and HF (volume ratio 10 : 4 : 1) resulted in the conversion of silicides into reactive silica. The resulant samples after the digestion were suitable for the silica analysis by ICP-AES. The ICP-AES results showed that the silica element could be readily determined with high accuracy (recovery was as high as 94.7–102.4%). This approach would enable a rapid analysis of the silica content in a non-wood lignocellulosic waste liquid, thus providing an approach for the comprehensive utilization of the spent liquid resource in a more efficient way.